Preparation method of melt-blown multilayer composite liquid filtering membrane
By preparing anti-aging agents and using coating materials, the performance of the meltblown multi-layer composite liquid filter membrane is improved, and the shortcomings of the existing membrane in terms of filtration accuracy, pollution resistance, regeneration ability, aging resistance and breathability are solved, and efficient and long-lasting filtration performance is achieved.
Patent Information
- Application Number
- CN202411743994.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-30
- Publication Date
- 2025-03-25
AI Technical Summary
The existing meltblown multi-layer composite liquid filter membranes have shortcomings in filtration accuracy, pollution resistance, regeneration ability, aging resistance and breathability, and are difficult to meet the needs of high-precision separation and long-term use.
The performance of meltblown multi-layer composite liquid filtration membrane is improved by preparing anti-aging agents, including modified lignin, highly dispersed zinc oxide and coating agents, and combined with the use of coating materials. Anti-aging agents improve the dispersion and binding power of zinc oxide to improve the aging resistance and pollution resistance of the membrane, while coating materials enhance the filtration accuracy and regeneration ability of the membrane.
The filtering accuracy, pollution resistance, regeneration ability, aging resistance and breathability of the meltblown multi-layer composite liquid filter membrane is significantly improved, and it meets the needs of high-precision separation and long-term use.
Smart Images

Figure CN119682160A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of liquid filtration membranes, and in particular to a method for preparing a melt-blown multi-layer composite liquid filtration membrane. Background Art
[0002] After solid particles are dispersed in liquid, they cannot sink quickly due to Brownian motion. At this time, the mixture of solid particles and liquid is called suspension. Suspensions often contain solid particles and impurities of different sizes, which need to be removed by effective filtration to improve the quality and purity of the product. Separation technology of suspension plays a vital role in many industrial fields, especially in chemical, mineral processing, food processing, water treatment and other industries.
[0003] Traditional separation methods for suspensions include sedimentation, centrifugal separation, chemical treatment, etc. Sedimentation uses the density difference between solid particles and liquid to separate solid particles from liquid; centrifugal separation uses centrifugal force to separate solid particles from liquid; chemical treatment uses chemical agents to change the surface properties of solid particles or cause particles to undergo chemical reactions, thereby achieving solid-liquid separation. However, the above separation methods all have the disadvantage of limited separation efficiency, and may not meet the requirements for occasions that require high-precision separation.
[0004] As a new type of filter material, melt-blown multi-layer composite liquid filter membrane has the advantages of high filtering accuracy, good air permeability, good corrosion resistance, etc., and is widely used in the separation of suspensions. However, the existing melt-blown multi-layer composite liquid filter membrane still has some shortcomings in preparation method and performance, specifically: First, the filtering accuracy of the existing melt-blown multi-layer composite liquid filter membrane is low, which is specifically manifested in the poor filtering ability of the existing melt-blown multi-layer composite liquid filter membrane for small-size solid particles; Second, the existing melt-blown multi-layer composite liquid filter membrane has poor anti-pollution ability and regeneration ability, which is specifically manifested in the fact that the existing melt-blown multi-layer composite liquid filter membrane is easy to adsorb pollutants during use, resulting in the existing melt-blown multi-layer composite liquid filter membrane being easily blocked by pollutants, and the processing ability of the suspension is reduced after blocking, and the processing ability of the suspension cannot be fully restored after regeneration; Third, the existing melt-blown multi-layer composite liquid filter membrane has poor aging resistance, which is specifically manifested in the fact that the existing melt-blown multi-layer composite liquid filter membrane is easy to age during use, and the filtering ability of the suspension is reduced after aging.
[0005] In order to solve the above problems, the most commonly used solutions are: first, to address the problem of low filtration accuracy, the pore size of the existing melt-blown multi-layer composite liquid filtration membrane is reduced, but the reduction in pore size will lead to a decrease in the air permeability of the existing melt-blown multi-layer composite liquid filtration membrane, and will also cause the existing melt-blown multi-layer composite liquid filtration membrane to be more easily clogged by pollutants during use, further resulting in the existing melt-blown multi-layer composite liquid filtration membrane. Anti-pollution ability and regeneration ability are deteriorated; second, to address the problem of poor anti-pollution ability and regeneration ability, a surface coating is added to the surface of the existing melt-blown multi-layer composite liquid filtration membrane, such as a nano-silicon dioxide-containing Surface coating is used to improve anti-pollution ability and regeneration ability, but the bonding force between the surface coating and the existing melt-blown multi-layer composite liquid filtration membrane is poor, and there is a problem of coating shedding during use, which further causes the aging resistance of the existing melt-blown multi-layer composite liquid filtration membrane to deteriorate; thirdly, in response to the problem of poor aging resistance, anti-aging agents and anti-ultraviolet agents are added to the preparation of the existing melt-blown multi-layer composite liquid filtration membrane, but excessive amounts of anti-aging agents and anti-ultraviolet agents added will affect the fluidity of the material, causing the diameter of the melt-blown fiber to be affected, further causing the filtration accuracy of the existing melt-blown multi-layer composite liquid filtration membrane to deteriorate. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a method for preparing a melt-blown multi-layer composite liquid filtration membrane, which can improve the filtration accuracy, anti-pollution ability, regeneration ability, aging resistance and air permeability of the melt-blown multi-layer composite liquid filtration membrane.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A method for preparing a melt-blown multi-layer composite liquid filtration membrane, comprising the following steps: preparing an anti-aging agent, preparing a coating material, preparing a first melt-blown cloth, preparing a second melt-blown cloth, preparing a third melt-blown cloth, and compounding; The preparation of the anti-aging agent comprises the following steps: preparing modified lignin, preparing highly dispersed zinc oxide, and coating; The modified lignin is prepared by adding alkali lignin, isopropanol and deionized water into a reactor with a reflux device, controlling the temperature of the reactor to 80-85°C, controlling the stirring speed to 100-300rpm, adding monobromododecane and concentrated hydrochloric acid, stirring and refluxing for 11-12h, adding sodium hydroxide to adjust the pH to 13.5-14, stirring and refluxing for 20-30min, filtering, taking the filtrate, adding concentrated hydrochloric acid to adjust the pH to 2-2.5, filtering, taking the filter residue, washing the filter residue with deionized water, and vacuum drying to obtain the modified lignin; In the preparation of the modified lignin, the usage ratio of alkali lignin, isopropanol, deionized water, monobromododecane, and concentrated hydrochloric acid is 65-70 g: 120-150 mL: 120-150 mL: 15-16 mL: 16-20 mL; The mass concentration of the concentrated hydrochloric acid is 38%; The method for preparing highly dispersed zinc oxide comprises mixing zinc oxide and deionized water, adding the mixture to an ultrasonic oscillator, controlling the frequency of the ultrasonic oscillator to be 20-25 kHz, and ultrasonically oscillating for 40-45 minutes. The mixture is then transferred to a reactor, the temperature in the reactor is controlled to be 10-40° C., the stirring speed is controlled to be 100-200 rpm, sodium lignin sulfonate is added, stirring for 50-60 minutes, centrifuging, taking a precipitate, washing the precipitate with deionized water, and vacuum drying to obtain highly dispersed zinc oxide. In the preparation of highly dispersed zinc oxide, the material ratio of zinc oxide, deionized water, and sodium lignin sulfonate is 190-200 g:4800-5200 mL:14-15 g; The average particle size of the zinc oxide is 100 nm; The coating comprises adding highly dispersed zinc oxide and butanediol into a reaction kettle, controlling the temperature in the reaction kettle to 10-40° C., controlling the stirring speed to 100-200 rpm, stirring for 20-30 min, adding modified lignin, stirring for 2.5-3 h, centrifuging, taking a precipitate, washing the precipitate with deionized water, and vacuum drying to obtain an anti-aging agent; In the coating, the usage ratio of highly dispersed zinc oxide, butanediol and modified lignin is 170-180g:3800-4000mL:17-20g; The preparation of the coating material comprises the following steps: preparing hydrophilic zinc oxide and mixing; The method for preparing hydrophilic zinc oxide comprises adding zinc chloride and a first portion of deionized water into a reactor, controlling the temperature in the reactor to 10-40° C., controlling the stirring speed to 100-200 rpm, stirring for 20-30 min, adding zinc oxide, stirring for 2-2.5 h, centrifuging, taking a precipitate, washing the precipitate with deionized water, vacuum drying, transferring the precipitate with a second portion of deionized water into a reactor, controlling the temperature in the reactor to 60-70° C., controlling the stirring speed to 100-200 rpm, stirring for 10-15 min, adding sodium alginate, stirring for 2-2.5 h, centrifuging, taking a precipitate, washing the precipitate with deionized water, and vacuum drying to obtain hydrophilic zinc oxide; In the preparation of the hydrophilic zinc oxide, the usage ratio of zinc chloride, the first portion of deionized water, zinc oxide, the second portion of deionized water, and sodium alginate is 28-30 g: 4000-4200 mL: 190-200 g: 4000-4200 mL: 32-35 g; The average particle size of the zinc oxide is 100 nm; The mixing is performed, and the silica sol, hydrophilic zinc oxide, and L-tyrosine are added into a reaction kettle, the temperature in the reaction kettle is controlled to 10-40° C., the stirring speed is controlled to 100-200 rpm, and the mixture is stirred for 2-2.5 hours to obtain a coating material; In the mixing, the amount ratio of silica sol, hydrophilic zinc oxide and L-tyrosine is 1300-1400 mL: 200-210 g: 24-26 g; The silica sol is an acidic silica sol with a pH of 3, a silicon dioxide content of 30%, and an average particle size of 20 nm; The first melt-blown cloth is prepared by adding polypropylene resin and anti-aging agent into a high-speed mixer and mixing them evenly, transferring them into a twin-screw extruder for melt extrusion, transferring them into a melt-blown device for melt spinning, performing high-temperature airflow stretching, performing hot pressing, and then completely immersing them in a coating material, standing at 15-40° C., taking them out, hanging them vertically, completely immersing them in anhydrous ethanol, standing at 30-40° C., taking them out, and drying them to obtain a first melt-blown cloth; In the preparation of the first melt-blown cloth, the mass ratio of the polypropylene resin to the anti-aging agent is 80-85:8-10; The melt temperature of the twin-screw extruder is 200-210°C; The temperature of the spinneret in the melt-blowing equipment is 245-255°C, the diameter of the spinneret hole is 0.3mm, and the aspect ratio is 15; The temperature of the high-temperature airflow is 230-240°C, and the stretching ratio is 25-30 times; The hot pressing temperature is 205-210°C and the time is 5-6 minutes; The drying temperature is 110-120°C; The polypropylene resin is a homopolymer polypropylene melt-blown material, and the melt index at 230° C. and 2.16 kg is 1000 g / 10 min; The first meltblown fabric has a grammage of 20-30 g / m 2 , thickness is 0.2-0.3mm, fiber diameter is 3-3.5μm; The second melt-blown cloth is prepared by adding polypropylene resin and anti-aging agent to a high-speed mixer and mixing them evenly, transferring them to a first twin-screw extruder for melt extrusion, transferring them to a first melt-blown device for melt spinning, and performing high-temperature air flow stretching to obtain fine fibers; adding polyester resin and anti-aging agent to a high-speed mixer and mixing them evenly, transferring them to a second twin-screw extruder for melt extrusion, transferring them to a second melt-blown device for melt spinning, and performing high-temperature air flow stretching to obtain coarse fibers; mixing the fine fibers with the coarse fibers and then performing hot pressing, controlling the hot pressing temperature to be 205-210° C. and the time to be 5-6 min, to obtain a second melt-blown cloth; In the preparation of the second melt-blown cloth, in the preparation of the fine fibers, the mass ratio of the polypropylene resin to the anti-aging agent is 80-85:14-16; The melting temperature of the first twin-screw extruder is 200-210°C; The temperature of the spinneret in the first melt-blowing device is 245-255° C., the diameter of the spinneret hole is 0.2 mm, and the aspect ratio is 12; The temperature of the high-temperature airflow during the high-temperature airflow stretching of the fine fibers is 230-240° C., and the stretching ratio is 30-40 times. In the preparation of crude fiber, the mass ratio of polyester resin to anti-aging agent is 80-85:10-11; The melt temperature of the second twin-screw extruder is 270-280°C; The temperature of the spinneret in the second melt-blowing device is 300-310°C, the diameter of the spinneret hole is 0.2mm, and the aspect ratio is 12; The temperature of the high-temperature airflow during the high-temperature airflow stretching of the fine fibers is 230-240° C., and the stretching ratio is 7-8 times. The hot pressing temperature is 205-210°C and the time is 5-6 minutes; The polypropylene resin is a homopolymer polypropylene melt-blown material, and the melt index at 230° C. and 2.16 kg is 1000 g / 10 min; The polyester resin is 300 g / 10 min at 230° C. and 2.16 kg; The weight of the second meltblown fabric is 40-50 g / m 2 , thickness is 0.5-0.6mm, diameter of coarse fiber is 15-20μm, diameter of fine fiber is 1-2μm; The mass ratio of polypropylene resin to polyester fiber is 75-80:100; The third melt-blown cloth is prepared by adding polypropylene resin and anti-aging agent into a high-speed mixer and mixing them evenly, transferring them into a twin-screw extruder for melt extrusion, transferring them into a melt-blown device for melt spinning, performing high-temperature airflow stretching, performing hot pressing, and then completely immersing them in a coating material, standing at 15-40° C., taking them out, hanging them vertically, completely immersing them in anhydrous ethanol, standing at 30-40° C., taking them out, and drying them to obtain a third melt-blown cloth; In the preparation of the third melt-blown cloth, the mass ratio of the polypropylene resin to the anti-aging agent is 80-85:8-10; The melt temperature of the twin-screw extruder is 200-210°C; The temperature of the spinneret in the melt-blowing equipment is 245-255°C, the diameter of the spinneret hole is 0.2 mm, and the aspect ratio is 12; The temperature of the high-temperature airflow is 230-240°C, and the stretching ratio is 30-40 times; The hot pressing temperature is 205-210°C and the time is 5-6 minutes; The drying temperature is 110-120°C; The polypropylene resin is a homopolymer polypropylene melt-blown material, and the melt index at 230° C. and 2.16 kg is 1000 g / 10 min; The first meltblown fabric has a grammage of 20-30 g / m 2 , thickness is 0.2-0.3mm, fiber diameter is 1-2μm; The composite comprises stacking the first meltblown cloth, the second meltblown cloth, and the third meltblown cloth from top to bottom and then hot-rolling and compounding them to obtain a composite meltblown cloth; In the compounding, the temperature of hot rolling compounding is 130-140° C. and the pressure is 180-200N.
[0008] Compared with the prior art, the present invention has the following beneficial effects: (1) The preparation method of the melt-blown multi-layer composite liquid filtration membrane of the present invention uses an anti-aging agent in the preparation of the first melt-blown cloth, the second melt-blown cloth, and the third melt-blown cloth. The preparation method of the anti-aging agent includes preparing modified lignin, preparing highly dispersed zinc oxide, and coating. The modified lignin is prepared by reacting alkali lignin with monobromododecane, and the dodecyl group replaces part of the phenolic hydroxyl groups in the alkali lignin to obtain a modified lignin containing dodecyl group. The highly dispersed zinc oxide is prepared by mixing zinc oxide with sodium lignin sulfonate to obtain highly dispersed zinc oxide with sodium lignin sulfonate adsorbed on the surface, thereby reducing the agglomeration of zinc oxide, improving the dispersibility of zinc oxide, and reducing the hydrophilicity of zinc oxide. The coating is mixed with highly dispersed zinc oxide and modified lignin, and the modified lignin is adsorbed on the surface of highly dispersed zinc oxide through intermolecular forces, thereby obtaining an anti-aging agent adsorbed with modified lignin. The antioxidant has zinc oxide as the core, sodium lignin sulfonate as the secondary outer layer, and modified lignin as the outermost layer, wherein zinc oxide can improve the reflection of the antioxidant to ultraviolet rays and improve the aging resistance of the prepared melt-blown multi-layer composite liquid filtration membrane, sodium lignin sulfonate can improve the binding force between zinc oxide and modified lignin, and can also promote the dispersion of zinc oxide, reduce the adsorption of zinc oxide to pollutants, and improve the anti-pollution ability of the prepared melt-blown multi-layer composite liquid filtration membrane, and the dodecyl group in the modified lignin can improve the compatibility and binding force between the antioxidant and polypropylene, avoid the influence of the antioxidant on the melt-blown process, and improve the filtration accuracy, regeneration ability and air permeability of the prepared melt-blown multi-layer composite liquid filtration membrane; in addition, the present invention also uses a coating material to treat the first melt-blown cloth and the third melt-blown cloth, and the preparation method of the coating material includes preparing hydrophilic zinc oxide and mixing, wherein the preparation of hydrophilic zinc oxide is to mix zinc chloride with zinc oxide, zinc oxide adsorbs zinc ions to obtain zinc oxide after adsorbing zinc ions, and then the oxygen after adsorbing zinc ions is The zinc oxide is mixed with sodium alginate, and the sodium alginate is cross-linked with the zinc ion, so that a layer of sodium alginate is coated on the surface of the zinc oxide to obtain hydrophilic zinc oxide coated with sodium alginate; the mixing is to mix the silica sol, the hydrophilic zinc oxide, and L-tyrosine to obtain a coating material; when the first melt-blown cloth and the third melt-blown cloth are impregnated with the coating material, the coating material is combined with the surface of the first melt-blown cloth and the third melt-blown cloth, and the silicon dioxide in the silica sol can form a hydrophilic silicon dioxide layer on the surface of the first melt-blown cloth and the third melt-blown cloth, and the L-tyrosine can form a hydrophilic silicon dioxide layer on the surface of the first melt-blown cloth and the third melt-blown cloth. Through the bridging effect, the benzene ring in L-tyrosine can form a π-π interaction with the lignin in the first melt-blown cloth and the third melt-blown cloth, and the amino group in L-tyrosine can form a hydrogen bond with the hydroxyl group in the silica sol, thereby improving the bonding force between the coating material and the first melt-blown cloth and the third melt-blown cloth, thereby improving the aging resistance of the prepared melt-blown multi-layer composite liquid filtration membrane; the coating material can also improve the filtration accuracy, anti-pollution ability and regeneration ability of the prepared melt-blown multi-layer composite liquid filtration membrane due to its hydrophilicity; (2) The preparation method of the melt-blown multi-layer composite liquid filtration membrane of the present invention can improve the filtration accuracy of the melt-blown multi-layer composite liquid filtration membrane. The filtration efficiency of the melt-blown multi-layer composite liquid filtration membrane prepared by the present invention for 1-2 μm particles is 97.5-98.4%; (3) The preparation method of the melt-blown multi-layer composite liquid filtration membrane of the present invention can improve the anti-pollution ability of the melt-blown multi-layer composite liquid filtration membrane. The pollution holding capacity of the melt-blown multi-layer composite liquid filtration membrane prepared by the present invention is 70-75g / m 2 ; (4) The preparation method of the melt-blown multi-layer composite liquid filtration membrane of the present invention can improve the air permeability of the melt-blown multi-layer composite liquid filtration membrane. The air permeability of the melt-blown multi-layer composite liquid filtration membrane prepared by the present invention is 2.3-2.5 mm / s; (5) The preparation method of the melt-blown multi-layer composite liquid filtration membrane of the present invention, the pure water flux of the prepared melt-blown multi-layer composite liquid filtration membrane is 4110-4326L / (m 2 h); (6) The preparation method of the melt-blown multi-layer composite liquid filtration membrane of the present invention can improve the regeneration capacity of the melt-blown multi-layer composite liquid filtration membrane. The melt-blown multi-layer composite liquid filtration membrane prepared by the present invention is used to treat a suspension. The average particle size of the solid particles in the suspension is 1 μm and the content is 2%. After continuous operation for 1 month, it is cleaned and regenerated. After cleaning and regeneration, the filtration efficiency for 1-2 μm particles is 97.2-98.2%, and the dirt holding capacity is 68-75 g / m 2 ; (7) The preparation method of the melt-blown multi-layer composite liquid filtration membrane of the present invention can improve the aging resistance of the melt-blown multi-layer composite liquid filtration membrane. After the melt-blown multi-layer composite liquid filtration membrane prepared by the present invention is placed in hot air at 85°C for 96 hours and then continuously irradiated with an ultraviolet lamp for 96 hours, the filtration efficiency for 1-2 μm particles is 96.5-98.1%, and the dirt holding capacity is 68-74 g / m 2 . BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 This is a scanning electron microscope image of the second meltblown cloth obtained in the step of preparing the second meltblown cloth in step 4 of Example 1. DETAILED DESCRIPTION
[0010] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0011] Example 1 A method for preparing a melt-blown multi-layer composite liquid filtration membrane, specifically comprising: 1. Preparation of anti-aging agent: (1) Preparation of modified lignin: 65 g of alkali lignin, 120 mL of isopropanol, and 120 mL of deionized water were added to a reactor with a reflux device, the temperature of the reactor was controlled to 80 ° C, the stirring speed was controlled to 100 rpm, 15 mL of monobromododecane and 16 mL of concentrated hydrochloric acid were added, and the mixture was stirred and refluxed for 11 h. Sodium hydroxide was added to adjust the pH to 13.5, and the mixture was stirred and refluxed for 20 min. The mixture was filtered, the filtrate was taken, concentrated hydrochloric acid was added to adjust the pH to 2, the mixture was filtered, the filter residue was taken, the filter residue was washed with deionized water, and vacuum dried to obtain the modified lignin. The mass concentration of the concentrated hydrochloric acid is 38%; (2) Preparation of highly dispersed zinc oxide: 190 g of zinc oxide and 4800 mL of deionized water were mixed and added to an ultrasonic oscillator. The frequency of the ultrasonic oscillator was controlled to 20 kHz. The mixture was ultrasonically oscillated for 40 min. The mixture was then transferred to a reactor. The temperature in the reactor was controlled to 10° C. The stirring speed was controlled to 100 rpm. 14 g of sodium lignin sulfonate was added. The mixture was stirred for 50 min. The mixture was centrifuged to obtain a precipitate. The precipitate was washed with deionized water and vacuum dried to obtain highly dispersed zinc oxide. The average particle size of the zinc oxide is 100 nm; (3) Coating: 170 g of highly dispersed zinc oxide and 3800 mL of butanediol were added into a reactor, the temperature in the reactor was controlled to 10 °C, the stirring speed was controlled to 100 rpm, and the mixture was stirred for 20 min. 17 g of modified lignin was added, and the mixture was stirred for 2.5 h. The mixture was centrifuged and the precipitate was taken. The precipitate was washed with deionized water and vacuum dried to obtain an anti-aging agent. 2. Preparation of coating materials: (1) Preparation of hydrophilic zinc oxide: Add 28 g zinc chloride and 4000 mL deionized water into a reactor, control the temperature in the reactor to 10° C., control the stirring speed to 100 rpm, stir for 20 min, add 190 g zinc oxide, stir for 2 h, centrifuge, take the precipitate, wash the precipitate with deionized water, vacuum dry, transfer it into a reactor with 4000 mL deionized water, control the temperature in the reactor to 60° C., control the stirring speed to 100 rpm, stir for 10 min, add 32 g sodium alginate, stir for 2 h, centrifuge, take the precipitate, wash the precipitate with deionized water, vacuum dry, and obtain hydrophilic zinc oxide; The average particle size of the zinc oxide is 100 nm; (2) Mixing: 1300 mL of silica sol, 200 g of hydrophilic zinc oxide, and 24 g of L-tyrosine were added into a reactor, the temperature in the reactor was controlled to 10° C., the stirring speed was controlled to 100 rpm, and the mixture was stirred for 2 h to obtain a coating material; The silica sol is an acidic silica sol with a pH of 3, a silicon dioxide content of 30%, and an average particle size of 20 nm; 3. Prepare the first melt-blown cloth: add polypropylene resin and anti-aging agent to a high-speed mixer in a mass ratio of 80:8 and mix them evenly, transfer them to a twin-screw extruder for melt extrusion, control the melting temperature of the twin-screw extruder to 200°C, transfer them to the melt-blown equipment for melt spinning, control the temperature of the spinneret in the melt-blown equipment to 245°C, the diameter of the spinneret hole to 0.3mm, the aspect ratio to 15, perform high-temperature air flow stretching, control the temperature of the high-temperature air flow to 230°C, the stretching ratio to 25 times, perform hot pressing, control the hot pressing temperature to 205°C, the time to 5min, and then completely immerse in the coating material, stand at 15°C for 4min, take out, hang vertically for 10min, completely immerse in anhydrous ethanol, stand at 30°C for 2h, take out, dry, and control the drying temperature to 110°C to obtain the first melt-blown cloth; The polypropylene resin is a homopolymer polypropylene melt-blown material, and the melt index at 230° C. and 2.16 kg is 1000 g / 10 min; The first meltblown fabric has a gram weight of 30 g / m 2 , thickness is 0.3 mm, fiber diameter is 3.5 μm; 4. Preparation of the second melt-blown cloth: Add polypropylene resin and anti-aging agent in a mass ratio of 80:14 to a high-speed mixer and mix evenly, transfer to the first twin-screw extruder for melt extrusion, control the melting temperature of the first twin-screw extruder to 200°C, transfer to the first melt-blown equipment for melt spinning, control the temperature of the spinneret in the first melt-blown equipment to 245°C, the diameter of the spinneret hole to 0.2mm, the aspect ratio to 12, perform high-temperature air flow stretching, control the temperature of the high-temperature air flow to 230°C, and the stretching ratio to 30 times to obtain fine fibers; Add polyester resin and anti-aging agent in a mass ratio of 80:10 is added to a high-speed mixer and mixed evenly, transferred to a second twin-screw extruder for melt extrusion, the melting temperature of the second twin-screw extruder is controlled to be 270°C, transferred to a second melt-blown device for melt spinning, the temperature of the spinneret in the second melt-blown device is controlled to be 300°C, the diameter of the spinneret hole is 0.2mm, the aspect ratio is 12, and high-temperature air flow stretching is performed, the temperature of the high-temperature air flow is controlled to be 230°C, and the stretching ratio is 7 times to obtain coarse fibers; the fine fibers are mixed with the coarse fibers and then hot-pressed, the hot-pressing temperature is controlled to be 205°C, and the time is 5min to obtain a second melt-blown cloth; The polypropylene resin is a homopolymer polypropylene melt-blown material, and the melt index at 230° C. and 2.16 kg is 1000 g / 10 min; The polyester resin is 300 g / 10 min at 230° C. and 2.16 kg; The weight of the second meltblown fabric is 50 g / m 2 , thickness is 0.6 mm, diameter of coarse fiber is 20 μm, diameter of fine fiber is 2 μm; The mass ratio of polypropylene resin to polyester fiber is 75:100; The second melt-blown fabric was subjected to scanning electron microscopy analysis, and the obtained scanning electron microscopy image is shown in Figure 1 ,Depend on Figure 1 It can be seen that the second melt-blown cloth contains coarse fibers and fine fibers, which are cross-distributed. The coarse fibers are polyester fibers, which can provide structure and rigidity, and the fine fibers are polypropylene fibers, which can improve the filtering function. 5. Preparation of the third melt-blown cloth: Add polypropylene resin and anti-aging agent to a high-speed mixer in a mass ratio of 80:8 and mix evenly, transfer to a twin-screw extruder for melt extrusion, control the melting temperature of the twin-screw extruder to 200°C, transfer to the melt-blown equipment for melt spinning, control the temperature of the spinneret in the melt-blown equipment to 245°C, the diameter of the spinneret hole to 0.2mm, the aspect ratio to 12, perform high-temperature air flow stretching, control the temperature of the high-temperature air flow to 230°C, the stretching ratio to 30 times, perform hot pressing, control the hot pressing temperature to 205°C, the time to 5min, and then completely immerse in the coating material, stand at 15°C for 4min, take out, hang vertically for 10min, completely immerse in anhydrous ethanol, stand at 30°C for 2h, take out, dry, and control the drying temperature to 110°C to obtain a third melt-blown cloth; The polypropylene resin is a homopolymer polypropylene melt-blown material, and the melt index at 230° C. and 2.16 kg is 1000 g / 10 min; The first meltblown fabric has a gram weight of 30 g / m 2 , thickness is 0.3 mm, fiber diameter is 2 μm; 6. Composite: The first meltblown cloth, the second meltblown cloth, and the third meltblown cloth are stacked from top to bottom and then hot-rolled to composite, and the temperature of the hot-rolled composite is controlled to be 130° C. and the pressure is 180N to obtain a composite meltblown cloth.
[0012] Example 2 A method for preparing a melt-blown multi-layer composite liquid filtration membrane, specifically comprising: 1. Preparation of anti-aging agent: (1) Preparation of modified lignin: 68 g of alkali lignin, 140 mL of isopropanol, and 140 mL of deionized water were added to a reactor equipped with a reflux device, the temperature of the reactor was controlled to 82 ° C, the stirring speed was controlled to 200 rpm, 15 mL of monobromododecane and 18 mL of concentrated hydrochloric acid were added, and the mixture was stirred and refluxed for 11.5 h, sodium hydroxide was added to adjust the pH to 13.5, and the mixture was stirred and refluxed for 25 min, filtered, the filtrate was taken, concentrated hydrochloric acid was added to adjust the pH to 2.2, filtered, the filter residue was taken, the filter residue was washed with deionized water, and vacuum dried to obtain the modified lignin; The mass concentration of the concentrated hydrochloric acid is 38%; (2) Preparation of highly dispersed zinc oxide: 195 g of zinc oxide and 5000 mL of deionized water were mixed and added to an ultrasonic oscillator. The frequency of the ultrasonic oscillator was controlled to 20 kHz. The ultrasonic oscillation was performed for 42 min. The mixture was then transferred to a reactor. The temperature in the reactor was controlled to 30 ° C. The stirring speed was controlled to 150 rpm. 14.5 g of sodium lignin sulfonate was added. The mixture was stirred for 55 min. The mixture was centrifuged to obtain a precipitate. The precipitate was washed with deionized water and vacuum dried to obtain highly dispersed zinc oxide. The average particle size of the zinc oxide is 100 nm; (3) Coating: 175 g of highly dispersed zinc oxide and 3900 mL of butanediol were added into a reactor, the temperature in the reactor was controlled to 20 °C, the stirring speed was controlled to 150 rpm, and the mixture was stirred for 25 min. 18 g of modified lignin was added, and the mixture was stirred for 2.5 h. The mixture was centrifuged and the precipitate was taken. The precipitate was washed with deionized water and vacuum dried to obtain an anti-aging agent. 2. Preparation of coating materials: (1) Preparation of hydrophilic zinc oxide: Add 29 g zinc chloride and 4100 mL deionized water into a reactor, control the temperature in the reactor to 20°C, control the stirring speed to 150 rpm, stir for 25 min, add 195 g zinc oxide, stir for 2 h, centrifuge, take the precipitate, wash the precipitate with deionized water, vacuum dry, transfer it into a reactor with 4100 mL deionized water, control the temperature in the reactor to 65°C, control the stirring speed to 150 rpm, stir for 12 min, add 34 g sodium alginate, stir for 2 h, centrifuge, take the precipitate, wash the precipitate with deionized water, vacuum dry to obtain hydrophilic zinc oxide; The average particle size of the zinc oxide is 100 nm; (2) Mixing: 1350 mL of silica sol, 205 g of hydrophilic zinc oxide, and 25 g of L-tyrosine were added into a reactor, the temperature in the reactor was controlled to 20° C., the stirring speed was controlled to 150 rpm, and the mixture was stirred for 2 h to obtain a coating material; The silica sol is an acidic silica sol with a pH of 3, a silicon dioxide content of 30%, and an average particle size of 20 nm; 3. Prepare the first melt-blown cloth: add polypropylene resin and anti-aging agent to a high-speed mixer in a mass ratio of 82:9 and mix evenly, transfer to a twin-screw extruder for melt extrusion, control the melting temperature of the twin-screw extruder to 205°C, transfer to a melt-blown device for melt spinning, control the temperature of the spinneret in the melt-blown device to 250°C, the diameter of the spinneret hole to 0.3mm, the aspect ratio to 15, perform high-temperature air flow stretching, control the temperature of the high-temperature air flow to 235°C, the stretching ratio to 28 times, perform hot pressing, control the hot pressing temperature to 205°C, the time to 5min, and then completely immerse in the coating material, stand at 20°C for 4min, take out, hang vertically for 10min, completely immerse in anhydrous ethanol, stand at 35°C for 2h, take out, dry, control the drying temperature to 115°C, and obtain the first melt-blown cloth; The polypropylene resin is a homopolymer polypropylene melt-blown material, and the melt index at 230° C. and 2.16 kg is 1000 g / 10 min; The first meltblown fabric has a grammage of 24 g / m 2 , thickness is 0.24 mm, fiber diameter is 3.2 μm; 4. Preparation of the second melt-blown cloth: Add polypropylene resin and anti-aging agent in a mass ratio of 82:15 to a high-speed mixer and mix evenly, transfer to the first twin-screw extruder for melt extrusion, control the melting temperature of the first twin-screw extruder to 205°C, transfer to the first melt-blown equipment for melt spinning, control the temperature of the spinneret in the first melt-blown equipment to 250°C, the diameter of the spinneret hole to 0.2mm, the aspect ratio to 12, perform high-temperature airflow stretching, control the temperature of the high-temperature airflow to 235°C, and the stretching ratio to 35 times to obtain fine fibers; Add polyester resin and anti-aging agent in a mass ratio of 82:10 is added to a high-speed mixer and mixed evenly, transferred to a second twin-screw extruder for melt extrusion, the melting temperature of the second twin-screw extruder is controlled to be 275°C, transferred to a second melt-blown device for melt spinning, the temperature of the spinneret in the second melt-blown device is controlled to be 305°C, the diameter of the spinneret hole is 0.2mm, the aspect ratio is 12, and high-temperature air flow stretching is performed, the temperature of the high-temperature air flow is controlled to be 235°C, and the stretching ratio is 8 times to obtain coarse fibers; the fine fibers are mixed with the coarse fibers and then hot-pressed, the hot-pressing temperature is controlled to be 205°C, and the time is 5min to obtain a second melt-blown cloth; The polypropylene resin is a homopolymer polypropylene melt-blown material, and the melt index at 230° C. and 2.16 kg is 1000 g / 10 min; The polyester resin is 300 g / 10 min at 230° C. and 2.16 kg; The weight of the second meltblown fabric is 44 g / m 2 , thickness is 0.53mm, diameter of coarse fiber is 17μm, diameter of fine fiber is 1.4μm; The mass ratio of polypropylene resin to polyester fiber is 78:100; 5. Preparation of the third melt-blown cloth: Add polypropylene resin and anti-aging agent to a high-speed mixer in a mass ratio of 82:9 and mix evenly, transfer to a twin-screw extruder for melt extrusion, control the melting temperature of the twin-screw extruder to 205°C, transfer to the melt-blown equipment for melt spinning, control the temperature of the spinneret in the melt-blown equipment to 250°C, the diameter of the spinneret hole to 0.2mm, the aspect ratio to 12, perform high-temperature air flow stretching, control the temperature of the high-temperature air flow to 235°C, the stretching ratio to 35 times, perform hot pressing, control the hot pressing temperature to 205°C, the time to 6min, and then completely immerse in the coating material, stand at 20°C for 4min, take out, hang vertically for 10min, completely immerse in anhydrous ethanol, stand at 35°C for 2h, take out, dry, and control the drying temperature to 115°C to obtain a third melt-blown cloth; The polypropylene resin is a homopolymer polypropylene melt-blown material, and the melt index at 230° C. and 2.16 kg is 1000 g / 10 min; The first meltblown fabric has a grammage of 24 g / m 2 , thickness is 0.24 mm, fiber diameter is 1.5 μm; 6. Composite: The first meltblown cloth, the second meltblown cloth, and the third meltblown cloth are stacked from top to bottom and then hot-rolled to composite, and the temperature of the hot-rolled composite is controlled to be 135° C. and the pressure is 190N to obtain a composite meltblown cloth.
[0013] Example 3 A method for preparing a melt-blown multi-layer composite liquid filtration membrane, specifically comprising: 1. Preparation of anti-aging agent: (1) Preparation of modified lignin: 70 g of alkali lignin, 150 mL of isopropanol, and 150 mL of deionized water were added to a reactor with a reflux device, the temperature of the reactor was controlled to 85 ° C, the stirring speed was controlled to 300 rpm, 16 mL of monobromododecane and 20 mL of concentrated hydrochloric acid were added, and the mixture was stirred and refluxed for 12 h. Sodium hydroxide was added to adjust the pH to 14, and the mixture was stirred and refluxed for 30 min. The mixture was filtered, the filtrate was taken, concentrated hydrochloric acid was added to adjust the pH to 2.5, the mixture was filtered, the filter residue was taken, the filter residue was washed with deionized water, and vacuum dried to obtain the modified lignin. The mass concentration of the concentrated hydrochloric acid is 38%; (2) Preparation of highly dispersed zinc oxide: 200 g of zinc oxide and 5200 mL of deionized water were mixed and added to an ultrasonic oscillator. The frequency of the ultrasonic oscillator was controlled to 25 kHz. The mixture was ultrasonically oscillated for 45 min. The mixture was then transferred to a reactor. The temperature in the reactor was controlled to 40° C. The stirring speed was controlled to 200 rpm. 15 g of sodium lignin sulfonate was added. The mixture was stirred for 60 min. The mixture was centrifuged and the precipitate was collected. The precipitate was washed with deionized water and vacuum dried to obtain highly dispersed zinc oxide. The average particle size of the zinc oxide is 100 nm; (3) Coating: 180 g of highly dispersed zinc oxide and 4000 mL of butanediol were added into a reactor, the temperature in the reactor was controlled to 40 °C, the stirring speed was controlled to 200 rpm, and the mixture was stirred for 30 min. 20 g of modified lignin was added, and the mixture was stirred for 3 h. The mixture was centrifuged and the precipitate was collected. The precipitate was washed with deionized water and vacuum dried to obtain an anti-aging agent. 2. Preparation of coating materials: (1) Preparation of hydrophilic zinc oxide: 30 g zinc chloride and 4200 mL deionized water were added to a reactor, the temperature in the reactor was controlled to 40°C, the stirring speed was controlled to 200 rpm, and the mixture was stirred for 30 min. 200 g zinc oxide was added, the mixture was stirred for 2.5 h, and the mixture was centrifuged to obtain a precipitate. The precipitate was washed with deionized water and then dried under vacuum. The mixture was transferred to a reactor with 4200 mL deionized water, the temperature in the reactor was controlled to 70°C, the stirring speed was controlled to 200 rpm, and the mixture was stirred for 115 min. 35 g sodium alginate was added, the mixture was stirred for 2.5 h, and the mixture was centrifuged to obtain a precipitate. The precipitate was washed with deionized water and then dried under vacuum to obtain hydrophilic zinc oxide. The average particle size of the zinc oxide is 100 nm; (2) Mixing: 1400 mL of silica sol, 210 g of hydrophilic zinc oxide, and 26 g of L-tyrosine were added into a reactor, the temperature in the reactor was controlled to 40° C., the stirring speed was controlled to 200 rpm, and the mixture was stirred for 2.5 h to obtain a coating material; The silica sol is an acidic silica sol with a pH of 3, a silicon dioxide content of 30%, and an average particle size of 20 nm; 3. Prepare the first melt-blown cloth: add polypropylene resin and anti-aging agent to a high-speed mixer in a mass ratio of 85:10 and mix evenly, transfer to a twin-screw extruder for melt extrusion, control the melting temperature of the twin-screw extruder to 210°C, transfer to a melt-blown device for melt spinning, control the temperature of the spinneret in the melt-blown device to 255°C, the diameter of the spinneret hole to 0.3mm, the aspect ratio to 15, perform high-temperature air flow stretching, control the temperature of the high-temperature air flow to 240°C, the stretching ratio to 30 times, perform hot pressing, control the hot pressing temperature to 210°C, the time to 6min, and then completely immerse in the coating material, stand at 40°C for 5min, take out, hang vertically for 11min, completely immerse in anhydrous ethanol, stand at 40°C for 2.5h, take out, dry, control the drying temperature to 120°C, and obtain the first melt-blown cloth; The polypropylene resin is a homopolymer polypropylene melt-blown material, and the melt index at 230° C. and 2.16 kg is 1000 g / 10 min; The first meltblown fabric has a gram weight of 20 g / m 2 , thickness 0.2 mm, fiber diameter 3 μm; 4. Preparation of the second melt-blown cloth: Add polypropylene resin and anti-aging agent in a mass ratio of 85:16 to a high-speed mixer and mix evenly, transfer to the first twin-screw extruder for melt extrusion, control the melting temperature of the first twin-screw extruder to 210°C, transfer to the first melt-blown equipment for melt spinning, control the temperature of the spinneret in the first melt-blown equipment to 255°C, the diameter of the spinneret hole to 0.2mm, the aspect ratio to 12, perform high-temperature air flow stretching, control the temperature of the high-temperature air flow to 240°C, and the stretching ratio to 40 times to obtain fine fibers; Add polyester resin and anti-aging agent in a mass ratio of 85:11 is added to a high-speed mixer and mixed evenly, transferred to a second twin-screw extruder for melt extrusion, the melting temperature of the second twin-screw extruder is controlled to be 280°C, transferred to a second melt-blown device for melt spinning, the temperature of the spinneret in the second melt-blown device is controlled to be 310°C, the diameter of the spinneret hole is 0.2mm, the aspect ratio is 12, and high-temperature air flow stretching is performed, the temperature of the high-temperature air flow is controlled to be 240°C, and the stretching ratio is 8 times to obtain coarse fibers; the fine fibers are mixed with the coarse fibers and then hot-pressed, the hot-pressing temperature is controlled to be 210°C, and the time is 6 minutes to obtain a second melt-blown cloth; The polypropylene resin is a homopolymer polypropylene melt-blown material, and the melt index at 230° C. and 2.16 kg is 1000 g / 10 min; The polyester resin is 300 g / 10 min at 230° C. and 2.16 kg; The weight of the second meltblown fabric is 40 g / m 2 , thickness is 0.5 mm, diameter of coarse fiber is 15 μm, diameter of fine fiber is 1 μm; The mass ratio of polypropylene resin to polyester fiber is 80:100; 5. Prepare the third melt-blown cloth: Add polypropylene resin and anti-aging agent to a high-speed mixer in a mass ratio of 85:10 and mix evenly, transfer to a twin-screw extruder for melt extrusion, control the melting temperature of the twin-screw extruder to 210°C, transfer to the melt-blown equipment for melt spinning, control the temperature of the spinneret in the melt-blown equipment to 255°C, the diameter of the spinneret hole to 0.2mm, the aspect ratio to 12, perform high-temperature air flow stretching, control the temperature of the high-temperature air flow to 240°C, the stretching ratio to 40 times, perform hot pressing, control the hot pressing temperature to 210°C, the time to 6min, and then completely immerse in the coating material, stand at 40°C for 5min, take out, hang vertically for 11min, completely immerse in anhydrous ethanol, stand at 40°C for 2.5h, take out, dry, and control the drying temperature to 120°C to obtain a third melt-blown cloth; The polypropylene resin is a homopolymer polypropylene melt-blown material, and the melt index at 230° C. and 2.16 kg is 1000 g / 10 min; The first meltblown fabric has a gram weight of 20 g / m 2 , thickness is 0.2 mm, fiber diameter is 1 μm; 6. Composite: The first meltblown cloth, the second meltblown cloth, and the third meltblown cloth are stacked from top to bottom and then hot-rolled to composite, and the temperature of the hot-rolled composite is controlled to be 140° C. and the pressure is 200N to obtain a composite meltblown cloth.
[0014] Comparative Example 1 Based on the preparation method of Example 2, the first step of preparing the anti-aging agent is omitted, and zinc oxide with an average particle size of 100 nm is used as a mass substitute for the addition of the anti-aging agent in the third step of preparing the first meltblown cloth, the fourth step of preparing the second meltblown cloth, and the fifth step of preparing the third meltblown cloth.
[0015] The rest of the technical solutions are consistent with those in Example 2.
[0016] Comparative Example 2 On the basis of the preparation method of Example 3, the step of preparing the coating material in step 2 is omitted, and the step of completely immersing the coating material and anhydrous ethanol is omitted in the step of preparing the first melt-blown cloth in step 3 and the step of preparing the third melt-blown cloth in step 5. Specifically, the step of preparing the first melt-blown cloth in step 3 is changed to: Add polypropylene resin and anti-aging agent in a mass ratio of 82:9 to a high-speed mixer and mix evenly, transfer to a twin-screw extruder for melt extrusion, control the melting temperature of the twin-screw extruder to 205°C, transfer to a melt-blown device for melt spinning, control the temperature of the spinneret in the melt-blown device to 250°C, the diameter of the spinneret hole to 0.3mm, the aspect ratio to 15, perform high-temperature airflow stretching, control the temperature of the high-temperature airflow to 235°C, the stretching ratio to 28 times, perform hot pressing, control the hot pressing temperature to 205°C, and the time to 5min to obtain a first melt-blown cloth; The polypropylene resin is a homopolymer polypropylene melt-blown material, and the melt index at 230° C. and 2.16 kg is 1000 g / 10 min; The first meltblown fabric has a gram weight of 21 g / m 2 , thickness is 0.22 mm, fiber diameter is 2.8 μm; Specifically, the step of preparing the third meltblown cloth in step 5 is changed to: Add polypropylene resin and anti-aging agent in a mass ratio of 82:9 to a high-speed mixer and mix evenly, transfer to a twin-screw extruder for melt extrusion, control the melting temperature of the twin-screw extruder to 205°C, transfer to a melt-blown device for melt spinning, control the temperature of the spinneret in the melt-blown device to 250°C, the diameter of the spinneret hole to 0.2mm, the aspect ratio to 12, perform high-temperature airflow stretching, control the temperature of the high-temperature airflow to 235°C, the stretching ratio to 35 times, perform hot pressing, control the hot pressing temperature to 205°C, and the time to 6 minutes to obtain a first melt-blown cloth; The polypropylene resin is a homopolymer polypropylene melt-blown material, and the melt index at 230° C. and 2.16 kg is 1000 g / 10 min; The first meltblown fabric has a gram weight of 20 g / m 2 , thickness is 0.22mm, and fiber diameter is 1.2μm.
[0017] The rest of the technical solutions are consistent with those in Example 2.
[0018] Performance Test 1 The filtration efficiency, dirt holding capacity, air permeability, and pure water flux of the melt-blown multilayer composite liquid filtration membrane prepared in Examples 1-3 and Comparative Examples 1-2 were tested for 1-2 μm particles. During the test, the first melt-blown cloth side was used as the water inlet side. The test results are as follows:
[0019] Performance Test 2 The melt-blown multilayer composite liquid filtration membrane prepared in Example 1-3 and Comparative Example 1-2 was used to treat a suspension, in which the average particle size of the solid particles in the suspension was 1 μm and the content was 2%. After continuous operation for 1 month, the membrane was cleaned and regenerated, and then the filtration efficiency and dirt holding capacity of the melt-blown multilayer composite liquid filtration membrane for 1-2 μm particles were tested. During the test, the first melt-blown cloth side was used as the water inlet side, and the test results were as follows:
[0020] Performance Test 3 The melt-blown multi-layer composite liquid filtration membranes prepared in Examples 1-3 and Comparative Examples 1-2 were placed in hot air at 85°C for 96 hours, and then continuously irradiated with an ultraviolet lamp for 96 hours, with the wavelength of the ultraviolet lamp controlled at 365 nm. The filtration efficiency and dirt holding capacity of the melt-blown multi-layer composite liquid filtration membranes for 1-2 μm particles were tested. During the test, the first melt-blown cloth side was used as the water inlet side, and the test results were as follows:
[0021] It can be seen from the above results that the filtration efficiency, dirt holding capacity, air permeability, pure water flux, regeneration capacity and aging resistance of Comparative Example 1 and Comparative Example 2 for 1-2 μm particles are all lower than those of Example 2.
[0022] Unless otherwise specified, all percentages used in the present invention are by mass.
[0023] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a melt-blown multi-layer composite liquid filtration membrane, characterized in that: The method comprises the following steps: preparing an anti-aging agent, preparing a coating material, preparing a first melt-blown cloth, preparing a second melt-blown cloth, preparing a third melt-blown cloth, and compounding; The preparation of the anti-aging agent comprises the following steps: preparing modified lignin, preparing highly dispersed zinc oxide, and coating; The preparation of the coating material comprises the following steps: preparing hydrophilic zinc oxide and mixing.
2. The method for preparing a melt-blown multi-layer composite liquid filtration membrane according to claim 1, characterized in that: The modified lignin is prepared by mixing alkali lignin, isopropanol and deionized water, stirring at 80-85° C., adding monobromododecane and concentrated hydrochloric acid, stirring and refluxing, adjusting the pH to 13.5-14, stirring and refluxing, filtering, taking the filtrate, adjusting the pH to 2-2.5, filtering, taking the filter residue, washing the filter residue, and vacuum drying to obtain the modified lignin; In the preparation of the modified lignin, the usage ratio of alkali lignin, isopropanol, deionized water, monobromododecane and concentrated hydrochloric acid is 65-70 g: 120-150 mL: 120-150 mL: 15-16 mL: 16-20 mL.
3. The method for preparing a melt-blown multi-layer composite liquid filtration membrane according to claim 1, characterized in that: The method for preparing highly dispersed zinc oxide comprises mixing zinc oxide and deionized water uniformly, stirring at 10-40° C., adding sodium lignin sulfonate, stirring, centrifuging, taking a precipitate, washing the precipitate, and vacuum drying to obtain highly dispersed zinc oxide; In the preparation of highly dispersed zinc oxide, the material ratio of zinc oxide, deionized water, and sodium lignin sulfonate is 190-200 g:4800-5200 mL:14-15 g; The average particle size of the zinc oxide is 100 nm.
4. The method for preparing a melt-blown multi-layer composite liquid filtration membrane according to claim 1, characterized in that: The coating comprises mixing highly dispersed zinc oxide and butanediol, stirring at 10-40° C., adding modified lignin, stirring, centrifuging, taking a precipitate, washing the precipitate, and vacuum drying to obtain an anti-aging agent; In the coating, the usage ratio of highly dispersed zinc oxide, butanediol and modified lignin is 170-180g:3800-4000mL:17-20g.
5. The method for preparing a melt-blown multi-layer composite liquid filtration membrane according to claim 1, characterized in that: The preparation of hydrophilic zinc oxide comprises mixing zinc chloride and a first portion of deionized water, stirring at 10-40° C., adding zinc oxide, stirring, centrifuging, taking a precipitate, washing the precipitate, and vacuum drying, mixing with a second portion of deionized water, stirring at 60-70° C., adding sodium alginate, stirring, centrifuging, taking a precipitate, washing the precipitate, and vacuum drying to obtain hydrophilic zinc oxide; In the preparation of the hydrophilic zinc oxide, the usage ratio of zinc chloride, the first portion of deionized water, zinc oxide, the second portion of deionized water, and sodium alginate is 28-30 g: 4000-4200 mL: 190-200 g: 4000-4200 mL: 32-35 g; The average particle size of the zinc oxide is 100 nm.
6. The method for preparing a melt-blown multi-layer composite liquid filtration membrane according to claim 1, characterized in that: The mixing comprises mixing the silica sol, hydrophilic zinc oxide and L-tyrosine, and stirring at 10-40° C. to obtain a coating material; In the mixing, the amount ratio of silica sol, hydrophilic zinc oxide and L-tyrosine is 1300-1400 mL: 200-210 g: 24-26 g; The silica sol is acidic silica sol with a pH of 3, a silicon dioxide content of 30%, and an average particle size of 20 nm.
7. The method for preparing a melt-blown multi-layer composite liquid filtration membrane according to claim 1, characterized in that: The first melt-blown cloth is prepared by adding polypropylene resin and anti-aging agent into a high-speed mixer and mixing them evenly, transferring them into a twin-screw extruder for melt extrusion, transferring them into a melt-blown device for melt spinning, performing high-temperature airflow stretching, performing hot pressing, and then completely immersing them in a coating material, standing at 15-40° C., taking them out, hanging them vertically, completely immersing them in anhydrous ethanol, standing at 30-40° C., taking them out, and drying them to obtain a first melt-blown cloth; In the preparation of the first melt-blown cloth, the mass ratio of the polypropylene resin to the anti-aging agent is 80-85:8-10; The melt temperature of the twin-screw extruder is 200-210°C; The temperature of the spinneret in the melt-blowing equipment is 245-255°C, the diameter of the spinneret hole is 0.3mm, and the aspect ratio is 15; The temperature of the high-temperature airflow is 230-240°C, and the stretching ratio is 25-30 times; The hot pressing temperature is 205-210°C and the time is 5-6 minutes; The drying temperature is 110-120°C; The polypropylene resin is a homopolymer polypropylene melt-blown material, and the melt index at 230° C. and 2.16 kg is 1000 g / 10 min.
8. The method for preparing a melt-blown multi-layer composite liquid filtration membrane according to claim 1, characterized in that: The second melt-blown cloth is prepared by adding polypropylene resin and anti-aging agent to a high-speed mixer and mixing them evenly, transferring them to a first twin-screw extruder for melt extrusion, transferring them to a first melt-blown device for melt spinning, and performing high-temperature air flow stretching to obtain fine fibers; adding polyester resin and anti-aging agent to a high-speed mixer and mixing them evenly, transferring them to a second twin-screw extruder for melt extrusion, transferring them to a second melt-blown device for melt spinning, and performing high-temperature air flow stretching to obtain coarse fibers; mixing the fine fibers with the coarse fibers and then performing hot pressing, controlling the hot pressing temperature to be 205-210° C. and the time to be 5-6 min, to obtain a second melt-blown cloth; In the preparation of the second melt-blown cloth, in the preparation of the fine fibers, the mass ratio of the polypropylene resin to the anti-aging agent is 80-85:14-16; The melting temperature of the first twin-screw extruder is 200-210°C; The temperature of the spinneret in the first melt-blowing device is 245-255° C., the diameter of the spinneret hole is 0.2 mm, and the aspect ratio is 12; The temperature of the high-temperature airflow during the high-temperature airflow stretching of the fine fibers is 230-240° C., and the stretching ratio is 30-40 times. In the preparation of crude fiber, the mass ratio of polyester resin to anti-aging agent is 80-85:10-11; The melt temperature of the second twin-screw extruder is 270-280°C; The temperature of the spinneret in the second melt-blowing device is 300-310°C, the diameter of the spinneret hole is 0.2mm, and the aspect ratio is 12; The temperature of the high-temperature airflow during the high-temperature airflow stretching of the fine fibers is 230-240° C., and the stretching ratio is 7-8 times. The hot pressing temperature is 205-210°C and the time is 5-6 minutes; The polypropylene resin is a homopolymer polypropylene melt-blown material, and the melt index at 230° C. and 2.16 kg is 1000 g / 10 min; The polyester resin is 300 g / 10 min at 230° C. and 2.16 kg; The mass ratio of polypropylene resin to polyester fiber is 75-80:
100.
9. The method for preparing a melt-blown multi-layer composite liquid filtration membrane according to claim 1, characterized in that: The third melt-blown cloth is prepared by adding polypropylene resin and anti-aging agent into a high-speed mixer and mixing them evenly, transferring them into a twin-screw extruder for melt extrusion, transferring them into a melt-blown device for melt spinning, performing high-temperature airflow stretching, performing hot pressing, and then completely immersing them in a coating material, standing at 15-40° C., taking them out, hanging them vertically, completely immersing them in anhydrous ethanol, standing at 30-40° C., taking them out, and drying them to obtain a third melt-blown cloth; In the preparation of the third melt-blown cloth, the mass ratio of the polypropylene resin to the anti-aging agent is 80-85:8-10; The melt temperature of the twin-screw extruder is 200-210°C; The temperature of the spinneret in the melt-blowing equipment is 245-255°C, the diameter of the spinneret hole is 0.2 mm, and the aspect ratio is 12; The temperature of the high-temperature airflow is 230-240°C, and the stretching ratio is 30-40 times; The hot pressing temperature is 205-210°C and the time is 5-6 minutes; The drying temperature is 110-120°C; The polypropylene resin is a homopolymer polypropylene melt-blown material, and the melt index at 230° C. and 2.16 kg is 1000 g / 10 min.
10. The method for preparing a melt-blown multi-layer composite liquid filtration membrane according to claim 1, characterized in that: The composite comprises stacking the first meltblown cloth, the second meltblown cloth, and the third meltblown cloth from top to bottom and then hot-rolling and compounding them to obtain a composite meltblown cloth; In the compounding, the temperature of hot rolling compounding is 130-140° C. and the pressure is 180-200N.
Citation Information
Cited By
Organic-solvent-resistant ultralight high-strength poly-PP composite filter material and preparation method thereof
CN121060169A
A polypropylene composite filter material resistant to organic solvents and its preparation method
CN121060169B